The mediating role of job satisfaction in the relationship between transformational leadership and organizational citizenship behavior among female civil servants in Central Java and Yogyakarta - Endah Sri Lestari; Reny Yuniasanti; Triana Noor Edwina Dewayani Soeharto; Hamzah Hazalizah (Universitas Mercu Buana Yogyakarta, 2025)
Female civil servants often have to divide their time between job demands and household responsibilities. While managing responsibilities at home, they’re also expected to perform optimally in the workplace, fully contribute to their organizations. This study explored how transformational leadership indirectly influences Organizational Citizenship Behavior (OCB) among female civil servants working in the regional government offices of Central Java and the Special Region of Yogyakarta (GO-CJ-DIY), with job satisfaction serving as a mediating variable in that relationship. The study used a total sampling technique with a population of 189 married female civil servants at GO-CJ-DIY who had been employed for more than three months. However, only 134 respondents completed the questionnaire and were therefore included in the final analysis. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed a path coefficient of 0.489, t = 8.252, p < 0.001, 95% CI [0.381, 0]. Keywords: Female Civil Servants; Job Satisfaction; Organizational Citizenship Behavior; Transformational Leadership.